STUDY ON THE LEGAL BASIS AS A MECHANISM FOR PREVENTION OF GAME FIXING IN FOOTBALL - K. Naydenova (Trakia Journal of Sciences)
Match fixing on worldwide scale today is a business and a matter of profit. In this connection, the purpose of our study is to find out if there are national normative measures in place to prevent the Game fixing. The main method used in the development of the report is the study and analysis of literary sources. The results of the conducted study on the basic normative documents and regulations of the Bulgarian Football Union show the presence of a number of measures with a preventive character, which are aimed at the prevention of game fixing. Conclusions: 1. Legislative texts with subsequent sanctions are provided in the Republic of Bulgaria to prevent the fixing of football matches. 2. The Chapter of the Penal Code of 2011 includes Chapter VIII A, which is "Crimes Against Sport", and in a proven case of fixing of a sporting event, provides for a sanction of one to six years' imprisonment and a fine of one thousand to ten thousand BGN. 3. In the disciplinary rules of the BFF, a text is provided which, in the case of a confirmed game fixing, provides for the suspension of the competitor's or the official's competitions for a period of at least 18 months and a pecuniary sanction of BGN 40000 for the respective football club.